Associations between Anterior Cruciate Ligament Injuries and Patella Alta and Trochlear Dysplasia in Adults Using Magnetic Resonance Imaging - Akgün, Ayşe Serap; Agirman, Mehmet (The Journal of Knee Surgery, 2020)
The aim of this study was to research the associations between anterior cruciate ligament (ACL) injuries and patella alta and trochlear dysplasia in adult patients using magnetic resonance imaging (MRI). This retrospective study included 221 adult patients: 110 with acute complete noncontact ACL tears and 111 without ACL injuries who underwent knee MRI procedures between May 2016 and July 2018. After the ACL injuries were verified using the sagittal proton density images, the patellar height and patellar tendon length were measured on the sagittal T1-weighted images, and the Insall–Salvati ratio (ISR) was calculated. In the axial proton density MRI scans, according to the Dejour and Le Coultre classification of trochlear dysplasia, the knees were classified as normal or as types A, B, C, or D. The patellar length was not significantly different between the patient and control groups (41.5 ± 3.3 vs. 41.0 ± 2.9 mm, respectively). An increased patellar tendon length (46.1 ± 3.9 vs. 44.5 ± 3.4 mm, respectively) and an increased ISR (1.11 ± 0.08 vs. 1.08 ± 0.06, respectively) were measured in the patient group (with the ACL tears). In the group with the ACL tears, the rate of trochlear dysplasia was higher (15.45%) than that in the healthy group (4.5%). Of the 17 trochlear dysplasia patients in the ACL group, 11 were type A (10%), 2 were type B (1.82%), 3 were type C (2.73%), and 1 was type D (0.91%). Results showed increased patellar tendon lengths, ISRs, and trochlear dysplasia in the patients with the ACL injuries when compared with the healthy control group. Although the causative relationship has not yet been clearly elucidated, one should keep in mind that these variations may be risk factors for ACL tears.
Keywords: anterior cruciate ligament; patella alta; trochlear dysplasia; magnetic resonance imaging